2011
DOI: 10.1038/nmat2986
|View full text |Cite
|
Sign up to set email alerts
|

Porphysome nanovesicles generated by porphyrin bilayers for use as multimodal biophotonic contrast agents

Abstract: Supplementary Methods Synthesis of pyropheophorbide-lipidIn a standard reaction, 100 nmol of 1-palmitoyl-2-hydroxy-sn-glycero-3-phosphocholine (Avanti Polar Lipids), 50 nmol pyropheophorbide (prepared from Spirulina Pacifica algae as described previously;Zheng et al., Bioconj. Chem., 2002, 13-392), 50 nmol of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide (Sigma), 25 nmol of 4-(dimethylamino) pyridine (Sigma) and 50 µL of N,Ndiisopropylethylamine (Sigma) were combined in 10 mL of anhydrous dichloromethane. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
955
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 1,246 publications
(995 citation statements)
references
References 40 publications
15
955
3
Order By: Relevance
“…Prior elegant works have demonstrated selective tumor imaging using activatable contrast agents, primarily of macroscopic tumors (17,28,29,(42)(43)(44). However, these probes have not been used to treat micrometastases, largely due to the fact that fluorescence-guided surgery is impractical at the microscopic scale.…”
Section: Resultsmentioning
confidence: 99%
“…Prior elegant works have demonstrated selective tumor imaging using activatable contrast agents, primarily of macroscopic tumors (17,28,29,(42)(43)(44). However, these probes have not been used to treat micrometastases, largely due to the fact that fluorescence-guided surgery is impractical at the microscopic scale.…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that liposomes incorporating porphyrin‐phospholipid (PoP) can be permeabilized by NIR light, releasing variable cargos such as Dox, calcein, sulforhodamine B, and gentamicin 208. PoP can be used to form nanoparticles with theranostic characters 214, 215, 216, 217, 218. PoP lipoosmes are thermostable, as PoP liposomes loaded with sulforhodamine B did not show cargo leakage in hot agarose before solidification.…”
Section: Nanoparticle‐mediated Cptmentioning
confidence: 99%
“…Abraxane, a novel 130‐nm, albumin‐bound particle form of paclitaxel, has also been designed to utilize endogenous albumin pathways to increase intratumor concentrations of the active drug 17. Promising multifunctional agents known as porphysomes (formed by the super‐assembly of porphyrin‐phospholipids) have recently been demonstrated as photothermal, photodynamic, and photoacoustic enhancement agents, as well as drug delivery vehicles 18, 19, 20. Ferritin, a ubiquitous protein in most living beings, has been utilized as a biodegradable platform for multimodality imaging 21.…”
Section: Introductionmentioning
confidence: 99%